2017
DOI: 10.1021/acs.biomac.7b00219
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization to Positively Charged Cellulose Nanocrystals Enhances the Antibacterial Activity and Stability of Hen Egg White and T4 Lysozyme

Abstract: Antibacterial bionanostructures were produced from cellulose nanocrystals (CNC) with immobilized lysozyme from hen egg white (HEW) and T4 bacteriophage, respectively. The nanocrystals were prepared from microcrystalline cellulose by ammonium persulfate oxidation with a yield of 68% and having an average size of 250 nm and low polydispersity index. HEW lysozyme (HEWL) and T4 lysozyme (T4L) were immobilized to CNC by different mechanisms including adsorption and covalent coupling to carbodiimide-activated carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…Our activity tests (Figure ) suggest the PEGylated T4L can be great potential antibacterial materials. Herein PEG protects the protein surface from the environment and T4L performs antibacterial functions . Our structural findings provides indications for optimizing the activity.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Our activity tests (Figure ) suggest the PEGylated T4L can be great potential antibacterial materials. Herein PEG protects the protein surface from the environment and T4L performs antibacterial functions . Our structural findings provides indications for optimizing the activity.…”
Section: Resultsmentioning
confidence: 87%
“…The Micrococcus lysodeikticus cells have been an effective platform to assess the antibacterial function of lysozymes . We, therefore, also employ the same approach to evaluate the activity on a total of 7 hybrids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Abouhmad et al showed that lysozyme can be covalently linked to the surface of amine‐functionalized cellulose nanocrystals. The positive charge of the nanocrystal is beneficial for the overall antibacterial activity . A drawback of the system is the lack of lysozyme protection, since it is fully exposed on the surface of the particles.…”
Section: Introductionmentioning
confidence: 99%